Changes in connectivity and local synchrony after cognitive stimulation – Intracerebral EEG study. (August 2018) - Klimes, Petr; Jurak, Pavel; Halamek, Josef; Roman, Robert; Chladek, Jan; Brazdil, Milan
Highlights: A method capable of analyzing dynamic changes in connectivity during cognitive tasks from different parts of the human brain. Changes in x-correlation with event-related power decrease/increase can help identify structures involved in cognitive task. Increase in connectivity and decrease in event-related power revealed local and distant synchrony pattern in the hippocampus. Abstract: Electroencephalographic studies utilize event-related power decrease/increase in order to analyze changes of neuronal activity in a single EEG channel during cognitive tasks. Other analytical approaches draw on bivariate methods which evaluate connectivity between two EEG channels. Despite the fact that spatial mapping of combined results of power and connectivity analyses may be used to study the dynamics of neuronal activation patterns, they are normally evaluated separately as different phenomena. Here we show the evaluation of dynamic changes in linear correlation after cognitive stimulation together with changes in power levels in the same channel pairs. Our results demonstrate the temporal evolution of synchronization patterns across the whole brain with a focus on the anatomical structure of the hippocampus. We observed a pattern of local and distant synchrony during cognitive processing, occurring 500 ms after stimulus onset in approximately 1% of all channel pairs. We hypothesize that evaluation of changes in connectivity, together with dynamic changes in power levels, can help identify dominant structures in the process of mental activity after a certain type of cognitive task. This can possibly lead to better understanding of synchronization processes at the neuronal and systemic level.